STUDENTS ATTENDANCE SYSTEM USING QR CODE - Noranual, Mohd Nor Aiman (Journal of Computing Technologies and Creative Content, 2019)
In today’s technologically advanced world, mobile phones are becoming more popular for users of any age than desktop or laptop computers. Knowing that smartphones are very popular among young people in the 20’s, so using smartphones to expedite the process of taking attendance by university educators will save time on learning and teaching as well as enhancing higher education processes. This project aimed to speed up the process of taking attendance by university instructors would save lecturing time and hence enhance the educational process. This paper proposes a QR code website system, which will be displayed in front of using smartboard displays, laptops or smartphones belonging to instructors for current students or at the beginning of each lecture. Therefore, students should be required to connect their smartphones with an Internet connection provided. Next, they can scan the code to confirm their presence. This paper describes the high-level implementation details of the proposed system. It also discusses how the system verifies the identity of the student to remove the fake registration and prevent fraud attendance. This attendance management system had been configured with three main modules which are website system, a server system and also database system. The final analysis of the project shows that this AttendItYourself project can offer the same features that other existing projects do and even better due to extra features. Also, the testing shows that the security of the database and system server is ensured, and the connection with the user running smoothly. The overall analysis concluded that the AttendItYourself project can be as efficient as a commercialized attendance management system in the market with a lower cost than the others.